Labor precarity and youth: Labor markets in Argentina, Brazil, Colombia, and Mexico - Florez-Vaquiro, Nelson (2025)
Labor precarity is a multidimensional phenomenon that severely affects youth in Latin America. Based on household survey data from Argentina, Brazil, Colombia, and Mexico from 2023, this article analyzes four dimensions of precarity: instability, lack of social protection, insufficient income, and underemployment. The results revealed that the salaried youth in Mexico and Argentina have the most precarious conditions, whereas Brazil showed the lowest levels of precarity. Precarity is most prevalent in Mexico, followed by Colombia and Argentina. In each of these countries, young women were the most affected, and there was an association between labor precarity, sociodemographic characteristics, and labor market structures. The youngest and those with lower levels of education are those who experience worse conditions. By sector of activity, in Mexico more problems are reported in the primary sector, whereas in Argentina, Brazil, and Colombia they occur in personal services. Young women, regardless of their level of education and sector of activity, report higher levels of precariousness, which aggravates gender inequality. The conclusions propose actions to promote the inclusion of young people in formal employment.